Market structure, mission drift and productivity towards a sustainable microfinance industry in Bangladesh / Md. Aslam Mia - Md. Aslam , Mia (2017)
Microfinance is a preferred development tool in most developing countries, and remains important to Bangladesh, the country where the sector is most established. With approximately half of the Bangladesh population is unbanked and one third below the income poverty line, microfinance serves as an important policy instrument in the country’s vision of attaining middle-income status by 2021. Hence, it is imperative for the microfinance industry to be effective, efficient and sustainable. This study identifies three important objectives – market structure, mission drift, and productivity – crucial to microfinance in the contemporary world. First, this study aims to investigate the market structure (concentration and competition) in order to understand functioning and the operations of the microfinance. Second, in recent years, financial interests have increasingly influenced microfinance institutions (MFIs), with financial gain overshadowing service to the poor. Hence, this study examines the incidence and explanations for commercial interests to interfere with the social mission of MFIs. Third, the long-run ability of MFIs to meet the financial needs of the poor is contingent on their economic viability. Thus, the productivity of MFIs and its determinants is assessed in this study. A balanced panel data set from 169 MFIs during the period of 2009 to 2014 which was compiled from annual reports by the Microcredit Regulatory Authority, Bangladesh is used for this purpose. Since the three objectives are independent of each other, different types of estimation strategies are employed based on convention and reported separately in different chapters. Based on the concentration ratio and the Herfindahl and Hirschman Index (structural approach), this study finds that the microfinance industry is moderately concentrated and currently transitioning to an unconcentrated market. The Lerner index (non-structural approach) confirmed that the competition level is relatively high and likely to follow an inverted U-shape during the study period. Results from the static and dynamic panel analysis, revealed that increased focus on commercial interest or profit motive leads to mission drift. Mission drift is also likely to happen when more commercial funds are injected into MFIs, as well as when MFIs are vulnerable to the macroeconomic and regulatory environment influences. The non-parametric Malmquist Productivity Index indicates that the microfinance industry in Bangladesh observed productivity progress, with a declining trend towards the end of the study period. Further decomposition results revealed that technical efficiency has enhanced overall productivity, while technological change has deteriorated. One policy implication that can be drawn from the evidence is to encourage MFIs participation in innovation activities, so that the stimulation of technological change can improve the overall productivity. The second stage parametric test revealed that GDP growth has a positive effect on productivity and technological progress, whereas an interest rate cap significantly deteriorates the productivity and technological progress of MFIs. Therefore, the policy makers and regulatory authority should consider macroeconomic and regulatory environment when designing policy prescriptions to promote sustainability in the microfinance industry.